Diverse Genotypes of Yersinia pestis Caused Plague in Madagascar in 2007. - Julia M Riehm; Michaela Projahn; Amy J Vogler; Minoaerisoa Rajerison; Genevieve Andersen; Carina M Hall; Thomas Zimmermann; Rahelinirina Soanandrasana; Voahangy Andrianaivoarimanana; Reinhard K Straubinger; Roxanne Nottingham; Paul Keim; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Yersinia pestis is the causative agent of human plague and is endemic in various African, Asian and American countries. In Madagascar, the disease represents a significant public health problem with hundreds of human cases a year. Unfortunately, poor infrastructure makes outbreak investigations challenging. METHODOLOGY/PRINCIPAL FINDINGS:DNA was extracted directly from 93 clinical samples from patients with a clinical diagnosis of plague in Madagascar in 2007. The extracted DNAs were then genotyped using three molecular genotyping methods, including, single nucleotide polymorphism (SNP) typing, multi-locus variable-number tandem repeat analysis (MLVA), and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) analysis. These methods provided increasing resolution, respectively. The results of these analyses revealed that, in 2007, ten molecular groups, two newly described here and eight previously identified, were responsible for causing human plague in geographically distinct areas of Madagascar. CONCLUSIONS/SIGNIFICANCE:Plague in Madagascar is caused by numerous distinct types of Y. pestis. Genotyping method choice should be based upon the discriminatory power needed, expense, and available data for any desired comparisons. We conclude that genotyping should be a standard tool used in epidemiological investigations of plague outbreaks.